PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR DALAM PEMBELAJARAN SENI BUDAYA MATERI SENI RUPA KELAS VIII DI SMP N 15 PADANG - RENO SATRIA WIJAYA, Dr.Yahya, M.Pd., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2018)
The research aim to to know influence of scientific approach to result learn class student of VIII in study of cultural art fine arts items in SMP N 15 Padang. Hypothesis Examinee in this research is result learn Cultural Art of Fine arts class student items of VIII SMP N 15 taught Padang by using scientific approach differ by signifikan with result learn Cultural Art taught Fine arts student items by using conventional study model. this Research type [is] sham experiment ( ekspermental quasi) with research racangan in the form of design group control posttest pretest. Population in this research [is] all class student of VIII SMP N 15 Padang which learn cultural art [of] fine arts items and enlist in the year Iesson 2017 / 2018 amounting to 219 student people. Sampel in this research use technique of purposive sampling from seven class selected with two that is class of class ekperimen VIII.6 and class control of VIII.2 with class masing masing there are 30 student people. Technique analyse this research data hypothesis test [pass/through] test of t real level 0.05. Result of research by experiment class using scientific approach show result learn high in comparison with student [at] control class using conventional study. Pursuant to examination of hypothesis by using test of t tes with program of SPSS version 16.00 obtained with t-result is 10.256 and t-tabel is 2.045 ( t-result> t-tabel) with level of signifikan 5% = 0,05) this shown that there are difference which [is] signifikan among/between both class. There by can be concluded that applying of scientific approach have an effect on positive to result learn class of VIII in study of ArtKeywords : scientific approach